2018
DOI: 10.24925/turjaf.v6i1.112-123.1661
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Anionic Detergent Concentration of Karasu Stream in Sinop (Turkey)

Abstract: The study was achieved between May 2014 and April 2015 at the Karasu Creek located in the province of Sinop. It was conducted to determine anionic detergent pollution and some physicochemical properties (pH, temperature, conductivity, salinity, dissolved oxygen, total hardness, chemical oxygen demand, phosphate PO4-3, total nitrogen). The anionic detergent concentration of the stations was determined on a monthly basis. Seasonally averaged values of the anionic detergent was measured as the highest value in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In the following month, an increase was observed in the ratio of OM and Chl-a which is important nutrition for mussels. Many studies on the Karasu Stream showed that seasonal trends did not change much over the years (Coşkun et al 2019;Gündoğdu et al 2018;Aydemir Çil et al 2016). Then, it can be argued that freshwater mussels live under relatively stable conditions resulted in a less stressful environment.…”
Section: Resultsmentioning
confidence: 99%
“…In the following month, an increase was observed in the ratio of OM and Chl-a which is important nutrition for mussels. Many studies on the Karasu Stream showed that seasonal trends did not change much over the years (Coşkun et al 2019;Gündoğdu et al 2018;Aydemir Çil et al 2016). Then, it can be argued that freshwater mussels live under relatively stable conditions resulted in a less stressful environment.…”
Section: Resultsmentioning
confidence: 99%
“…Oil and grease were measured through a separating funnel using n-Hexane, COD was measure through the Open Re ux method, BOD 5 was measure digital meter, ionic detergent was measure through colorimetric methods (Gündoğdu et al 2018, Hussain et al 2021. For toxic trace elements, a 50 mL leachate sample was transferred to a beaker and reduce the volume up to 15-20 mL through heating.…”
Section: Experimental Workmentioning
confidence: 99%
“…Detergent contains the chemicals which when enter the water in high concentrations capable of harming the human body and causing eutrophication of the lake [Pattusamy et al 2013]. Detergents can cause changes in water properties and are active in water systems because they increase solubility in water [Gundogdu, et al 2018]. Detergents play an important role in increasing pollution from household wastewater, agricultural runoff in the form of herbicide and insecticide residues, and from certain industries [El-Gawad, 2014].…”
Section: Detergentmentioning
confidence: 99%